Psychologically informed physical therapy for musculoskeletal pain: current approaches, implications, and future directions from recent randomized trials - Coronado, Rogelio A. (Pain Rep, 2020)
Psychologically informed physical therapy (PIPT) blends psychological strategies within a physical therapist's treatment approach for the prevention and management of chronic musculoskeletal pain. Several randomized trials have been conducted examining the efficacy of PIPT compared to standard physical therapy on important patient-reported outcomes of disability, physical function, and pain. In this review, we examine recent trials published since 2012 to describe current PIPT methods, discuss implications from findings, and offer future directions. Twenty-two studies, representing 18 trials, were identified. The studied PIPT interventions included (1) graded activity or graded exposure (n = 6), (2) cognitive-behavioral-based physical therapy (n = 9), (3) acceptance and commitment-based physical therapy (n = 1), and (4) internet-based psychological programs with physical therapy (n = 2). Consistent with prior reviews, graded activity is not superior to other forms of physical activity or exercise. In a few recent studies, cognitive-behavioral-based physical therapy had short-term efficacy when compared to a program of standardized exercise. There is a need to further examine approaches integrating alternative strategies including acceptance-based therapies (ie, acceptance and commitment therapy or mindfulness) or internet-based cognitive-behavioral programs within physical therapy. Although PIPT remains a promising care model, more convincing evidence is needed to support widespread adoption, especially in light of training demands and implementation challenges.